Communications and Multimedia Security 12th IFIP TC 6 / TC 11 International Conference, CMS 2011, Ghent, Belgium, October 19-21,2011. Proceedings - Decker, Bart De; Lapon, Jorn; Naessens, Vincent; Uhl, Andreas (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 12th IFIP TC 6/TC 11 International Conference on Communications and Multimedia Security, CMS 2011, held in Ghent, Belgium, in October 2011. The 26 revised papers presented were carefully reviewed and selected from 52 submissions. The papers are organized in topical sections on usability, architecture and framework security, mobile identity management, secure hardware platforms, biometrics, multimedia security, network security and authentication.